Evaluación de la diversidad forestal en el centro de producción e investigación Pablo Yacu - Arévalo Luján, Doris Maribel (2012)
The present thesis work to obtain the professional title of Environmental Engineer has as title: "Porest diversity evaluation in the Pabloyacu center of production and investigation, 2011 ", it considers to evaluate the forest diversity and to know the number of individuals for species, likewise to determine the principal characteristics of the area of study. This work of investigation centred on the forest investigation in order to apply the indexes of diversity. It was considered important to realize a study of the physical aspect using the management tool " Ecological and Economic Zoning " using the information systems geographical, this it is detailed in the results, where they identified a sandy loam soil in greater proportion; as well well as the determination of population parameters. Por this investigation Gentry method was in use applying the technology Estratificadamente at random. It consists in placing 1 O transects of 2m x 50m for each sampling unit, making a total of 0.1ha. In each transect is proceeded to identify and quantify the species present, it was also considered biometric data and description ofthe study area. In the results of the investigation there was identified that the most representative species is the Rupiña with 41 individuals, this demonstrates his wide distribution in the evaluated transectos. The índices of diversity are shaped by the diversity Alpha, Beta and Gamma. Por purposes of the investigation it was considered the Alpha and Beta diversity. In the alpha diversity we have that the species richness is low with a value of 7. 29 In the indexes of Margalef and Menhinick respective! y. In Chao 2 it was determined that 29% is represented by the species present in a single sample and 24% is represented by species present in both samples. According to the Jacknife 1 formula of the occurrence ofthe species in a single sample is high with 51.8, in Jacknife 2 is high with a value of 54.28. Using the Chao 1 formula has to be 46% ofthe sampled species are represented by one or two individuals. The Simpson index is very important, because it shows the dominance of a species within the framework of all the sampled population, where it is believed that the probability of occurrence oftwo randomly chosen species is 0.07, this implies a high diversity of species in the sample. Berger-Parker's index determined that the forest diversity is high. The index of Shannon Wiener indicates us that the area of investigation is diverse, this agrees with Simpson's index. In Pielou's index one determined that it is abundant with a value ofO. 843. Beta diversity has the Jaccard index shows that the species found and identified are very diversificas between if. With the index of Sokal and Sneath is 0.09 , which means that the species found in the different transects are common in a 9 per cent, that is to say the sites are different in their composition. Finally the complementarity ofthe species ofthe transects is 0.73 this indicates the importance ofpreserving the forest.